Productivity, inequality, and the digital economy : a transatlantic perspective - Greenan, Nathalie; L'Horty, Yannick; Mairesse, Jacques (MIT Press, 2002)
Essays on the computer and the economy, particularly in relation to employment rates and to wage inequality. The widespread diffusion of information and communication technologies (ICT) has had controversial, seemingly paradoxical consequences. ICT are viewed as driving growth and employment in the United States, while contributing to European unemployment and the so-called Eurosclerosis. At the same time, both the United States and Europe have seen increased wage inequalities between skilled and unskilled workers. This book explores the computer's puzzling effects on the economy, at both the micro and macro levels. The contributions include data from field work, small samples of firms, and national surveys of management practice; econometric studies; and macroeconomic theoretical analysis.